Use of 20% Mannitol in Patients with Hemorrhagic Stroke - Ayatullah Malik; Atiqah Luthfiyah; Desvica Fitriyani Putri; Ryma Fauzana; Andini Putri; Sheren Ariesta; Raysa Afma; Rozi Thoyyiba; Nida Nurul; Selvi Putri Alin (CV. AFDIFAL MAJU BERKAH, 2026)
This case report describes the clinical course, management, and outcome of a 70-year-old male patient diagnosed with hemorrhagic stroke with intracerebral hemorrhage in the right basal ganglia, accompanied by intraventricular hemorrhage and cerebral edema. The patient presented with left-sided weakness, slurred speech, facial asymmetry, and decreased level of consciousness. Comprehensive management included intravenous fluids, osmotic diuretics (mannitol), antifibrinolytics (tranexamic acid), vitamin K, neuroprotective agents (citicoline), antibiotics, and supportive therapies. Despite decompressive craniectomy and intensive care, the patient’s neurological status progressively deteriorated from compos mentis to coma. Monitoring showed unstable vital signs, impaired coagulation parameters, and fluctuating blood glucose levels. No significant drug-related problems or adverse reactions were identified during treatment. However, the severity of brain injury, increased intracranial pressure, and associated complications led to poor clinical outcomes. The patient was declared deceased on January 25, 2026. This case highlights the importance of early intervention, continuous monitoring, and comprehensive management in hemorrhagic stroke patients.